Dynamics and plasma properties of an X-ray jet from SUMER, EIS, XRT, and EUVI A & B simultaneous observations super() - Madjarska, MS (Astronomy and astrophysics (Berlin), 2010)
Context. Small-scale transient phenomena in the quiet Sun are believed to play an important role in coronal heating and solar wind generation. One of them, called “ X-ray jet” , is the subject of our study. Aims. We intend to investigate the dynamics, evolution, and physical properties of this phenomenon. Methods. We combine multi-instrument observations obtained simultaneously with the SUMER spectrometer onboard SoHO, with EIS and XRT onboard Hinode, and with EUVI/SECCHI onboard the Ahead and Behind STEREO spacecrafts. We derive plasma parameters such as temperatures and densities as well as dynamics by using spectral lines formed in the temperature range from 10  000 K to 12 MK. We also use an image difference technique to investigate the evolution of the complex structure of the studied phenomenon. Results. With the available unique combination of data we were able to establish that the formation of a jet-like event is triggered by not one, but several energy depositions, which are most probably originating from magnetic reconnection. Each energy deposition is followed by the expulsion of pre-existing or newly reconnected loops and/or collimated flow along open magnetic field lines. We derived in great detail the dynamic process of X-ray jet formation and evolution. For the first time we also found spectroscopically a temperature of 12 MK (Fe xxiii 263.76 Å ) and density of 4 × 10 super(10) cm super(-3) in the quiet Sun, obtained from a pair of Fe xii lines with a maximum formation temperature of 1.3 × 10 super(6) K, in an energy deposition region. We point out a problem concerning an uncertainty in using the SUMER Mg x 624.9 Å   line for coronal diagnostics. We clearly identified two types of up-flow: one collimated up-flow along open magnetic field lines and a plasma cloud formed from the expelled BP loops. We also report a cooler down-flow along closed magnetic field lines. A comparison is made with a model developed by Moreno-Insertis et al.  (2008).